A protocol for a systematic review of non-randomised evaluations of strategies to improve participant recruitment to randomised controlled trials. Issue 1 (December 2016) - Gardner, Heidi; Fraser, Cynthia; MacLennan, Graeme; Treweek, Shaun
Abstract Background Randomised controlled trials guard against selection bias and therefore offer the fairest way of evaluating healthcare interventions such as medicinal products, devices and services. Recruitment to trials can be extremely difficult, and poor recruitment can lead to extensions to both time and budget and may result in an underpowered study which does not satisfactorily answer the original research question. In the worst cases, a trial may be abandoned, causing huge waste. The evidence to support the choice of recruitment interventions is currently weak. Non-randomised evaluations of recruitment interventions are currently rejected on grounds of poor methodological quality, but systematic evaluation and assessment of this substantial body of work (using Grading of Recommendations Assessment, Development and Evaluation (GRADE) where possible) may provide useful information to support and inform the recruitment decisions of trialists and the research priorities of methodology researchers. Methods The following databases will be searched for relevant studies: Cochrane Methodology Register, MEDLINE, EMBASE, CINAHL and PsycINFO. Any non-randomised study that includes a comparison of two or more interventions to improve recruitment to randomised controlled trials will be included. We will not apply any restrictions on publication date, language or journal. The primary outcome will be the number of individuals or centres recruited into a randomised controlled trial. The secondary outcome will be cost per recruit. Two reviewers will independently screen abstracts for eligible studies, and then, full texts of potentially relevant records will be reviewed. Disagreements will be resolved through discussion. The methodological quality of studies will be assessed using the Cochrane risk of bias tool for non-randomised studies, and the GRADE system will be used if studies are pooled. Discussion This review aims to summarise the evidence on methods used to improve recruitment to randomised controlled trials. Carrying out a systematic review including only data from non-randomised studies is a novel approach, and one which some may argue is futile. However, we believe that the systematic evaluation of what is likely to be a substantial amount of research activity is necessary, worthwhile, and will yield valuable results for the clinical trials community regardless of whether the outcomes find in favour of one or more interventions. Should the results of this review suggest that non-randomised evaluations do have something to offer trialists planning their recruitment strategies, the review may be combined in the future with the Cochrane review of randomised evaluations to produce a full review of recruitment strategies encompassing both randomised and non-randomised evaluation methods. Systematic review registration PROSPEROCRD42016037718